Integration of Earth-based materials in 3D concrete printing (3DCP): Physico-chemical and Technological characterization - Oulkhir Fatima-Zahra; Rihani Nadir; Akhrif Iatimad; El Jai Mostapha (E3S Web of Conferences)
The overall goal of this study is to support the advancement of new construction methods and materials that are more cost-effective and have lower carbon emissions. There is a rising interest in utilizing earth materials in 3DCP for sustainable construction solutions, but their progress is limited by slow production rates. This research investigated the influence of various parameters on the efficacy of 3D earth materials printing using Taguchi experimental design, such as alginate dosing, scan strategy, scan speed, layer thickness, and curing age. Moreover, the impact of incorporating 2% alginate biopolymer into the clay matrix was assessed through FTIR and XRD analysis. Additionally, the Taguchi method was assessed using Fault Tree Analysis FTA to pinpoint the primary causes of failure in extrud- ability and buildability functions.